2005
DOI: 10.1080/01926230490523978
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Induced Renal Interstitial Fibrosis in Neonatal Rats, Developing as Solitary Nephron Unit Lesions

Abstract: Cisplatin (CDDP)-induced renal lesions in rats prove a useful model for analysis of the pathogenesis of post-tubular injury-renal interstitial fibrosis. This study investigated the histopathological changes in 10-day-old neonatal rats induced by a single injection of CDDP (4.5 mg/kg). Compared with age-matched controls, on postinjection (PI) days 1 to 6, the number of apoptotic cells, demonstrable with TUNEL method, was significantly increased in CDDP-treated neonates, and there was no marked epithelial necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
(114 reference statements)
1
21
0
Order By: Relevance
“…ED1-positive cells may be responsible for production of TNF-α and TGF-β1 in the early stages, leading to the induction of myofibroblastic cells 25,56 . In fact, α-SMApositive myofibroblastic cell number begins to increase with increased number of ED1-positive cells in the acute and chronic models 6,25,26 . ED2 is used to detect resident macrophages 17,27,30,34 .…”
Section: Roles Of Macrophagesmentioning
confidence: 99%
See 3 more Smart Citations
“…ED1-positive cells may be responsible for production of TNF-α and TGF-β1 in the early stages, leading to the induction of myofibroblastic cells 25,56 . In fact, α-SMApositive myofibroblastic cell number begins to increase with increased number of ED1-positive cells in the acute and chronic models 6,25,26 . ED2 is used to detect resident macrophages 17,27,30,34 .…”
Section: Roles Of Macrophagesmentioning
confidence: 99%
“…Compared with cisplatin-injected adult rats that develop extensive interstitial fibrosis in the corticomedullary junction, the formation of fibrotic lesions induced in neonatal rats by a single injection of cisplatin (4.5 mg/kg) is delayed, and the lesions are limited to the area around the affected nephrons 26 . In the neonatal lesions, ED1-, ED2-and OX6-positive cells also appear mainly around the dilated tubules.…”
Section: Macrophage Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have demonstrated that cisplatin-induced nephrotoxicity is associated with the activation of apoptosis, inflammation and fibrosis pathways [2]. A single injection of cisplatin may induce renal epithelial cell damage, epithelial-to-mesenchymal transition (EMT), and progressive interstitial fibrosis, along with an upregulation of transforming growth factor-β1 (TGF-β1) [3], [4]. Cisplatin may activate pro-apoptotic genes and repress anti-apoptotic genes by transcriptional regulation [5].…”
Section: Introductionmentioning
confidence: 99%